Association Between Working Hours and Poor Glycemic Control in Patients With Diabetes: The Kangbuk Samsung Health Study. Issue 10 (2nd October 2022) - Seo, Eunhye; Lee, Yesung; Lee, Woncheol
Abstract : Long working hours were positively associated with an increased risk of poor glycemic control in patients with diabetes, aged over 40 years and undergoing treatment. Working hours for the workers with uncontrolled diabetes can be an important factor in glycemic control. Therefore, workers who work long hours may need more supervision and effort to glycemic control. Abstract : Objective: This study aimed to evaluate the relationship between working hours and glycemic control. Methods: Study was performed among Korean participants who underwent at least two health screening examinations between 2012 and 2018. The study included 2169 participants who were older than 40 years and undergoing treatment for diabetes at baseline. A hemoglobin A1c level >9% at the follow-up visit was defined as poor glycemic control. The weekly working hours were divided into three groups for analysis. Results: Compared with participants with 45–54 weekly working hours, multivariate-adjusted hazard ratios (95% confidence intervals) for incident poor glycemic control among participants with ≥55 and 35–44 working hours were 1.40 (1.01–1.96) and 1.51 (1.09–2.09), respectively. Conclusions: Standard working hours and long working hours were independent risk factors for poor diabetes control in patients with diabetes.